DOP57 GLP-1 based therapies and risk of Inflammatory Bowel Disease: real world evidence from a nationwide cohort study. (30th January 2023) - Christensen, H S; Andersen, D; Jess, T; Allin, K H
Abstract: Background: Glucagon-like peptide-1 (GLP-1) based therapies, including GLP-1 receptor agonists (GLP-1RA) and dipeptidyl peptidase-4 inhibitors (DPP4i), are incretin therapies used to treat type 2 diabetes. In addition to incretin effects, GLP-1 based therapies exhibit anti-inflammatory effects. Nevertheless, a previous study reported increased risk of inflammatory bowel disease (IBD) associated with DPP4i use, while two other studies reported no altered risk. No previous studies have investigated the use of GLP-1RA and risk of IBD. In this study we investigated whether use of GLP-1 based therapies alters the risk of developing IBD among individuals with type 2 diabetes. Methods: In the setting of a prospective Danish nationwide cohort study (January 1, 2007 - December 31, 2018), we applied a new user active comparator design to compare the risk of IBD in users of GLP-1 based therapies with users of other glucose-lowering drugs. Considering exposure to GLP-1 based therapies as a time-varying covariate, we used a Cox proportional hazards model adjusted for sex, age, socio-economic status, urbanisation, and metformin use to estimate hazard ratios (HRs) of IBD. Results: Among 177, 950 new users of glucose-lowering drugs, 412 individuals developed IBD during a median follow-up period of 4.84 (95% CI 4.82 to 4.87) years. We found no altered risk of IBD associated with the use of GLP-1 based therapies with an adjusted HR of 0.96 (95% CI 0.72 to 1.27). Adjusted HRs of IBD were 1.30 (95% CI 0.86 to 1.96) for new users of GLP-1RA and 0.84 (95% CI 0.59 to 1.19) for new users of DPP4i compared to new users of other glucose lowering drugs. Findings were consistent in all analyses, including separate analyses of Crohn's disease and ulcerative colitis. Conclusion: In a population-based cohort of individuals with type 2 diabetes, we did not find an altered risk of IBD associated with the overall use of GLP-1 based therapies. Specifically, we did not confirm the previously reported increased risk of IBD associated with DPP4i. The influence of GLP-1RA on IBD needs further examination.